Modified protocol for pterygium surgery without blades and electrocoagulation - Ge, Huimin; Cao, Guofan; Wang, Jian; Zhang, Shu (Frontiers in Medicine, 2025)
PurposeTo evaluate the efficacy, safety, and outcomes of a blade- and cautery-free surgical protocol for pterygium removal.MethodsPterygium removal surgery was done in 69 eyes (67 patients; 24 males and 43 females) who were followed up for at least 6 months. The surgery was characterized by blunt separation of the pterygium from the head to the limbal arc using the tip of Vannas scissors and modified procedures, such as transpositional flapping and suture closure. Neither a blade nor a cautery was used.ResultsThe reported subjects were 60.7 years old on average, and most of them had primary pterygium (66 out of 69). The proposed surgical protocol was simple to perform, requiring an average operation time of 18.7 min which was shorter than that of the suture and fibrin glue groups mentioned in relevant reports. Post-anesthesia pain was relieved quickly 1 day after surgery without the use of pain killers. During the follow-up period of 11.3 ± 3.1 months, recurrence of pterygium requiring additional surgery was seen in only three eyes (4.3%).ConclusionThe potential of the examined protocol as an easy, efficient, and reliable approach was demonstrated.